2020
DOI: 10.1111/rda.13642
|View full text |Cite
|
Sign up to set email alerts
|

Role of mRNAs and long non‐coding RNAs in regulating the litter size trait in Chuanzhong black goats

Abstract: Fecundity improvement is one of the most important objectives for goat breeders as it can considerably greatly increase production efficiency. The molecular mechanisms underlying fecundity in goats remain largely unknown. To explore the molecular and genetic mechanisms related to the fecundities and prolificacies in Chuanzhong black goats, we performed high‐throughput RNA sequencing to identify differentially expressed long non‐coding RNAs (lncRNAs) and mRNAs (DElncRNAs and DEmRNAs, respectively) the ovaries o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…LncRNAs have been reported to engage the epigenetic or transcriptional regulation of neighboring genes as cis or trans-elements [ 21 ]. This type of regulatory capacity can be demonstrated in several reproductive processes, such as LOC102191297 and LOC102171967 targeting SRD5A2 in the steroid hormone biosynthesis pathway to regulate goat reproduction [ 22 ], and Lnc5926 targeting ZSCAN4 and EIF1AX , which are essential for early embryonic development [ 23 ]. Importantly, numerous works have proved that lncRNA expression can lead to early germ cell formation and embryo implantation, and the process of mammalian animal reproduction [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…LncRNAs have been reported to engage the epigenetic or transcriptional regulation of neighboring genes as cis or trans-elements [ 21 ]. This type of regulatory capacity can be demonstrated in several reproductive processes, such as LOC102191297 and LOC102171967 targeting SRD5A2 in the steroid hormone biosynthesis pathway to regulate goat reproduction [ 22 ], and Lnc5926 targeting ZSCAN4 and EIF1AX , which are essential for early embryonic development [ 23 ]. Importantly, numerous works have proved that lncRNA expression can lead to early germ cell formation and embryo implantation, and the process of mammalian animal reproduction [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have demonstrated that lncRNAs play a vital role in reproductive processes (Taylor et al, 2015), including sex hormone responses (Yang et al, 2013), oocyte meiosis (Yang et al, 2020), and ovulation (Lian et al, 2020). Emerging evidence from humans has identified the roles of lncRNAs in reproduction-related systems (Wang and Qin, 2019) and as key regulators of the normal development of granulosa cells (Tu et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The mRNA expression profile of ovary between uniparous and multiparous Anhui white goats [ 24 ], the miRNA expression in Chuanzhong black goat ovarian stroma and follicles [ 25 ], circRNA expression difference in pre-ovulatory ovarian follicles between Boer goat and Macheng black goat [ 26 ], and lncRNA expression difference in ovary of Anhui white goat at different estrous cycle periods [ 14 ], have been investigated by sequencing in previous studies, which provide resources for studies on goat fertility. Moreover, the mRNA and lncRNA databases of goat ovary in Chuanzhong black goat between high- and low-fecundity goats have also been analyzed [ 27 ]. However, the coalition analysis between each database is not reported in goat.…”
Section: Introductionmentioning
confidence: 99%